Design and structure–property relationship of benzothienoisoindigo in organic field effect transistors1. Issue 75 (19th August 2015) - Hasegawa, Tsukasa; Ashizawa, Minoru; Matsumoto, Hidetoshi
<x xml:space="preserve">Abstract</x> A novel planar π-conjugated small molecule, benzothienoisoindigo (BTII), in which additional benzene rings are fused with the thieoisoindigo (TII) unit, has been designed and synthesized.